Identificationof a novel linear epitope on the porcine reproductive and respiratory syndrome virus nucleocapsid protein, as recognized by a specific monoclonal antibody - Cheng, Yuening; Wu, Miaoli; Xiao, Li; Zhang, Mengdi; Huang, Bihong; Cong, Feng; Yi, Li (Frontiers in Immunology, 2023)
Introduction Porcine reproductive and respiratory syndrome virus (PRRSV) remains one of the most threatening pathogens of swine. The nucleocapsid (N) protein is the major structural protein of the virus and has been used as a PRRSV diagnostic antigen due to its high level of inherent immunogenicity. Methods The recombinant PRRSV N protein was generated by the prokaryotic expressing system and used to immunized mice. Monoclonal antibodies against PRRSV were produced and validated by western blot analysis and indirect immunofluorescence analysis. In this study, the linear epitope of a specific monoclonal antibody mAb (N06) was subsequently identified by enzyme-linked immunosorbent assays (ELISA) using the synthesized overlapping peptides as antigens. Results According to the results of western blot analysis and indirect immunofluorescence analysis, mAb (N06) was capable of recognizing the native form as well as the denatured form of PRRSV N protein. The results of ELISA showed that mAb N06 recognized the epitope NRKKNPEKPHFPLATE, which was consistent with BCPREDS predictions of antigenicity. Conclusion All the data suggested that the mAb (N06) can be used as diagnostic reagents for PRRSV detection, while the recognized linear epitope can be useful in epitope-based vaccines development, which is helpful for the control of local PRRSV infections in swine.